Pathological Personality Traits ( DSM-5 ), Risk Factors, and Mental Health - Gongora, Vanesa Carina (2017)
This study aimed to evaluate the psychometric properties of the brief version of the Personality Inventory for DSM-5 (PID-5-BF) in a community sample of Argentine adult population, to establish its relationship with the Big Five normal personality traits, and to examine the association of pathological traits with mental and physical maladaptiveness assessed through the level of mental health and World Health Organization (WHO) health risk factors. The sample consisted of 1,032 subjects from the metropolitan area of Buenos Aires. The PID-5-BF, the Big Five Inventory, the Mental Health Continuum?Short Form, and the Survey on risk factors for noncommunicable diseases were used. A five-factorial structure that explained 59.48% of the variance was found, with reliability values higher than α = .86 for each factor. Convergences among pathological personality traits and the five-factor personality model were found, except for Psychoticism and Openness to experience. The severity of personality traits was associated with low levels of mental health and higher number of WHO health risk factors. Nevertheless, the associations among these variables were low to moderate.